2021
DOI: 10.3389/fpsyg.2021.644020
|View full text |Cite
|
Sign up to set email alerts
|

On the Factors Influencing Green Purchase Intention: A Meta-Analysis Approach

Abstract: This study systematically analyzes the factors that affect consumers’ green purchase intention. Through a comprehensive literature review, the influencing factors of consumers’ green purchase intention are organized into three categories: cognitive factors, consumer individual characteristics, and social factors. Next, a meta-analysis of 54 empirical papers was conducted using Comprehensive Meta-Analysis 3.0 software to quantitatively assess these relationships. The results revealed that green perceived value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
178
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(208 citation statements)
references
References 96 publications
18
178
1
11
Order By: Relevance
“…Barber, Taylor and Strick [70] and Asih, et al [77] also examined that attitude determines environmental knowledge and GP purchase intentions. In recent years, Paul, Modi and Patel [71] researched Indian customers wherein attitude significantly predicts GP purchase intentions, others have also investigated it [78,79]. Mostafa [63] analyzed whether customers with a positive attitude remain more receptive to purchase GP.…”
Section: Attitude Towards Green Brands and Green Purchase Intentionmentioning
confidence: 99%
“…Barber, Taylor and Strick [70] and Asih, et al [77] also examined that attitude determines environmental knowledge and GP purchase intentions. In recent years, Paul, Modi and Patel [71] researched Indian customers wherein attitude significantly predicts GP purchase intentions, others have also investigated it [78,79]. Mostafa [63] analyzed whether customers with a positive attitude remain more receptive to purchase GP.…”
Section: Attitude Towards Green Brands and Green Purchase Intentionmentioning
confidence: 99%
“…Hence, comprehending consumers and developing green marketing strategies to entice targeted consumers have become common research topics. Past studies showed that many companies have begun implementing green marketing strategies to meet consumers' needs and gain a larger market for green products to achieve long-term business profits (Dangelico & Vocalelli, 2017;Sdrolia & Zarotiadis, 2019;Zhuang et al, 2021). Similarly, environmental issues have become a new scenario for the businesses in Malaysia to participate in green activities as part of their social responsibility and transformation programme (Aslam et al, 2020;Ahmed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research on this topic began in the 1970s, with researchers from Sweden, Japan, and the UK contributing significantly to the subject over the past decade. Previous research has focused on the green purchase behavior [32,33], change and diversity in patterns of usage, policies calling for a behavior change [34,35], and green consumption [36,37]. The World Population Review [38] expresses the importance of achieving SD through choices, lifestyles, and behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%